RELEVANSI PRINSIP-PRINSIP EKONOMI DAN AKUNTANSI TERHADAP QS. AL-BAQARAH AYAT 282 - Amir Amir; Ahmad Afin; Aisyatul Badriyah (Fakultas Syariah dan Ekonomi Islam Universitas Ibrahimy, 2024)
This article explains that Islam has a significant role in regulating the relationship and interaction between humans and God as well as fellow humans, other creatures, and the environment through the rules of muamalah. The concept of accounting in Islam, known as al-muhasābah, is included in the realm of muamalah which is related to the ability of the human mind. Accounting is the measurement, description, or provision of certainty regarding financial information that helps decision-making in companies, organizations, and government agencies. The Qur'an has explained the basic concept of accounting long before the introduction of the concept of double-entry bookkeeping economic and accounting by Lucas Pacioli. Surah Al-Baqarah verse 282 outlines the concept of accounting which emphasizes responsibility or accountability in muamalah. This verse emphasizes the importance of recording transactions correctly, openness, and justice between the two parties. This research uses library research method to identify and analyze the relevance of economic and accounting principles with verse 282 in the Qur'an. In the letter, there are three relevant accounting principles: accountability, fairness, and truth. The principle of accountability emphasizes the importance of each party involved in the transaction to be responsible for their actions. The principle of justice emphasizes correct and fair recording, while the principle of truth creates fairness in recognizing, measuring, and reporting economic transactions. Thus, the relationship of economic accounting principles with verse 282 of the Qur'an confirms the importance of integrity, fairness, and obedience in economic activities in accordance with Islamic values. This study aims to strengthen the understanding of the relevance of accounting principles to Islamic teachings, so as to contribute to the development of business practices that are in accordance with Islamic value